Principal Management In Improving The QualityOf Education Personnel - Undang Ruslan Wahyudin; Ridwan Irwansyah; Hinggil Permana; Gesti Meriani; Annisa Rahmawati (Journal of Pedagogi, 2024)
This research aims to identify the principal's management in improving the quality of educational staff at SMAN 5 Karawang. Improving the quality of educational staff is important in improving the quality of education in schools. SMAN 5 Karawang is one of the senior high schools that has a good reputation in Karawang, but it still needs to be studied further regarding the quality management of the educational staff that is implemented. This research uses a qualitative descriptive research method with data collection techniques through observation, interviews and documentation studies. Informants consisted of school principals, education staff, teachers and students at SMAN 5 Karawang. The collected data was analyzed using qualitative data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of this research indicate that SMAN 5 Karawang has implemented effective education staff quality management. This management includes developing the professionalism of educational staff through training and development, using performance evaluation as a monitoring and development tool, providing rewards and punishments, as well as efforts to improve communication and cooperation between educational staff, students and parents